Circulating oncometabolite 2-hydroxyglutarate is a potential surrogate biomarker in patients with isocitrate dehydrogenase-mutant intrahepatic cholangiocarcinoma - Borger, Darrell R; Goyal, Lipika; Yau, Thomas; Poon, Ronnie T; Ancukiewicz, Marek; Deshpande, Vikram; Christiani, David C; Liebman, Hannah M; Yang, Hua; Kim, Hyeryun; Yen, Katharine; Faris, Jason E; et al. (Clinical cancer research, 2014)
Mutations in the IDH1 and IDH2 (IDH1/2) genes occur in approximately 20% of intrahepatic cholangiocarcinoma and lead to accumulation of 2-hydroxyglutarate (2HG) in the tumor tissue. However, it remains unknown whether IDH1/2 mutations can lead to high levels of 2HG circulating in the blood and whether serum 2HG can be used as a biomarker for IDH1/2 mutational status and tumor burden in intrahepatic cholangiocarcinoma. We initially measured serum 2HG concentration in blood samples collected from 31 patients with intrahepatic cholangiocarcinoma in a screening cohort. Findings were validated across 38 resected patients with intrahepatic cholangiocarcinoma from a second cohort with tumor volume measures. Circulating levels of 2HG were evaluated relative to IDH1/2 mutational status, tumor burden, and a number of clinical variables. Circulating levels of 2HG in the screening cohort were significantly elevated in patients with IDH1/2-mutant (median, 478 ng/mL) versus IDH1/2-wild-type (median, 118 ng/mL) tumors (P < 0.001). This significance was maintained in the validation cohort (343 ng/mL vs. 55 ng/mL, P < 0.0001) and levels of 2HG directly correlated with tumor burden in IDH1/2-mutant cases (P < 0.05). Serum 2HG levels ≥170 ng/mL could predict the presence of an IDH1/2 mutation with a sensitivity of 83% and a specificity of 90%. No differences were noted between the allelic variants IDH1 or IDH2 in regard to the levels of circulating 2HG. This study indicates that circulating 2HG may be a surrogate biomarker of IDH1 or IDH2 mutation status in intrahepatic cholangiocarcinoma and that circulating 2HG levels may correlate directly with tumor burden. Clin Cancer Res; 20(7); 1884-90. ©2014 AACR.